A genética no ensino de biologia: sua história, importância, desafios e adaptações metodológicas em consonância com a revolução digital - Moraes, Clarissa de Souza (Universidade Federal de São Carlos, 2023)
Genetics has always been one of the most complex, controversial and fundamental blocks in Biological Sciences for the understanding of biological processes, permeated with history in the scientific field, with characters who represent great achievements for humanity, such as Ernst Haeckel, Johann Friedrich Miescher, Richard Altman, Rosalind Franklin, Francis Crick, James Watson, Franklin W. Stahl, Matthew Meselson, Har Gobind Khorana, Marshall W. Nirenberg Paul C. Zamecnik, the Tsuneko couple and the Reiji Okazaki couple inspire interest and curiosity from science enthusiasts. Considered a "master key" for young people who aspire to a profession in the area, genetics and its teaching in today's society, represents a great challenge for students with regard to understanding the contents due to the amount of theories, meanings, interconnections and abstract dimension and little connection to the social life of young people. In order to bring together all the content concerning genetics - its history, interdisciplinarity, social, economic and environmental importance - making it more accessible and didactic in the classroom, the review addresses technology as an ally in correcting failures and difficulties in the teaching-learning of young people. In addition, the review articulates the problematization inherent in the responsibility of the mediating educator and the Universities, in view of the amount of unreliable information on the internet and/or with a lack of seriousness and scientific basis on the internet and media used by young people in search of information, both for school studies, as well as for academic research
Genetics in biology teaching: its history, importance, challenges and methodological adaptations in line with the digital revolution
Keywords: Ensino-aprendizagem de genética; Tecnologias educacionais; Educação; Education; Education technologies; Genetics learning-teaching; CIENCIAS BIOLOGICAS